Legal Education on The Prevention of Criminal Violence In Household During The Covid-19 Pandemic - Margie Gladies Sopacua (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Violence against wives that occurs in the household is not only experienced and found in the public area, but is also very popular in the domestic area which is categorized as a form of violence contained in the Law on the Elimination of Domestic Violence (UU PKDRT).Purposes of Devotion: Providing understanding to the communityin Kawatu Hamlet, West Seram District (SBB), regarding domestic violence and the efforts made to prevent domestic violence. Method of Devotion: The method used is legal counseling to the community about efforts to prevent domestic violence in Kawatu Hamlet, West Seram District (SBB).Results of the Devotion: Implementation of PKM activities in Kawatu Hamlet, West Seram District (SBB) it can be found and it is known that prevention efforts against criminal acts of domestic violence include preventive efforts. This effort is made to build public awareness of domestic violence.